2013
DOI: 10.3724/sp.j.1037.2011.00420
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF EQUAL--CHANNEL ANGULAR PRESSING ON THE MICROSTRUCTURES AND TENSILE PROPERTIES OF 18Ni(C--250) MARAGING STEEL

Abstract: An 18Ni (C-250) maraging steel was successfully processed by equal-channel angular pressing (ECAP) for a single pass at room temperature. After ECAP deformation, the peak aging time was cut obviously and the peak strength of the steel was enhanced about 100 MPa. Microstructural observations showed that the martensite laths of 18Ni maraging steel were elongated to more narrow bands with a width of 100-200 nm after ECAP deformation, and the width of martensite lath was not affected by the subsequent aging treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Luo et al [16] proposed that refined martensite sub-grains (packets, blocks or laths) contributed to the improved impact toughness by acquiring finer retained austenite in an ultra-high-strength stainless steel. Han et al [17] revealed that much finer prior austenite subjected to multi-stage forging could increase the impact toughness of 18Ni(250) maraging steel. The above indicates that the synergistic toughening of metastable austenite and a hierarchical maraging matrix can effectively resolve the dilemma of inverse strength-toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [16] proposed that refined martensite sub-grains (packets, blocks or laths) contributed to the improved impact toughness by acquiring finer retained austenite in an ultra-high-strength stainless steel. Han et al [17] revealed that much finer prior austenite subjected to multi-stage forging could increase the impact toughness of 18Ni(250) maraging steel. The above indicates that the synergistic toughening of metastable austenite and a hierarchical maraging matrix can effectively resolve the dilemma of inverse strength-toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there exist some problems for traditional austenitic grain (γ) refinement technology of maraging steels. Firstly, some severe plastic deformation technology, such as equal channel angular process (ECAP) [18,19] and high pressure torsion (HPT) can effectively reduce the grain (γ) size. However, a large amount of crystal defects will also be introduced so that the toughening effect is weakened.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [6][7][8], we reported that equal-channel angular pressing (ECAP) method was very effective in the refinement of the lath size, and lath width could be readily controlled during the multi-pass ECAP process. Accordingly, the yield strength of maraging steel was significantly enhanced by refining lath width down into nano-order via ECAP technique.…”
Section: Introductionmentioning
confidence: 99%